Brain MRI Reveals Ascending Atrophy in Parkinson's Disease Across Severity - Blair, Jamie C.; Barrett, Matthew J.; Patrie, James; Flanigan, Joseph L.; Sperling, Scott A.; Elias, W. Jeffrey; Druzgal, T. Jason (Frontiers in Neurology, 2019)
Models which assess the progression of Lewy pathology in Parkinson’s disease have proposed ascending spread in a caudal-rostral pattern. In-vivo human evidence for this theory is limited, in part because there are no biomarkers that allow for direct assessment of Lewy pathology. Here, we measured neurodegeneration via MRI, an outcome which may serve as a proxy for a more direct assessment of ascending models using a combination of 1) MRI-based measures of grey matter density and 2) regions of interest (ROIs) corresponding to cortical and subcortical loci implicated in past MRI and stereological studies of Parkinson’s disease. Grey matter density was measured using brain MRI voxel-based morphometry from three cohorts: 1) early Parkinson’s disease, 2) more advanced Parkinson’s disease and 3) healthy controls. Early Parkinson’s disease patients (N=228, mean age=61.9 years, mean disease duration=0.6 years) were newly diagnosed by the Parkinson’s Progression Markers Initiative (PPMI). Advanced Parkinson’s disease patients (N=136, mean age=63.5 years, mean disease duration=8.0 years) were collected retrospectively from a local cohort undergoing evaluation for functional neurosurgery. Control subjects (N=103, mean age=60.2 years) were from PPMI. Comparative analyses focused on grey matter regions ranging from deep grey subcortical structures to the neocortex. ROIs were defined with existing probabilistic cytoarchitectonic brain maps. For subcortical regions of the basal forebrain, amygdala, and entorhinal cortex, advanced Parkinson’s disease patients had significantly lower grey matter density when compared to both early Parkinson’s disease and healthy controls. No differences were seen in neocortical regions that are “higher” in any proposed ascending pattern. Across early and advanced Parkinson’s disease, grey matter density from nearly all subcortical regions significantly decreased with disease duration; no neocortical regions showed this effect. These results demonstrate that atrophy in advanced Parkinson’s patients compared to early patients and healthy controls is largely confined to subcortical grey matter structures. The degree of atrophy in subcortical brain regions was linked to overall disease duration, suggesting an organized pattern of atrophy across severity.